2010
DOI: 10.1080/03079451003767261
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antimicrobial resistance of recentSalmonella entericaserovar Gallinarum isolates from chickens in South Korea

Abstract: Salmonella enterica serovar Gallinarum isolates (n 0105) from chickens in South Korea between 2002 and 2007 were tested for antimicrobial susceptibility by determining minimum inhibitory concentrations of 16 antimicrobials, and their predominant resistance profiles were genetically characterized. Most isolates (99/ 105; 94.3%) were resistant to nalidixic acid and resistant/intermediately resistant to fluoroquinolones, and 63.8% (67/105) of the isolates were resistant to three or more antimicrobials. Forty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
0
19
1
1
Order By: Relevance
“…In South Korea, no resistance to fluoroquinolones was detected in S. Gallinarum isolates from chickens from 1995 (LEE et al 2004), however a number of isolates from 2001 were reported resistant to fluoroquinolones showing an increased MIC that ranged from 2 to 8 µg/ml (KANG et al 2010). Our results also suggest an increasing resistance to this class of antibiotics, especially in S. Gallinarum which was statistically different from the levels detected in older isolates (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, no resistance to fluoroquinolones was detected in S. Gallinarum isolates from chickens from 1995 (LEE et al 2004), however a number of isolates from 2001 were reported resistant to fluoroquinolones showing an increased MIC that ranged from 2 to 8 µg/ml (KANG et al 2010). Our results also suggest an increasing resistance to this class of antibiotics, especially in S. Gallinarum which was statistically different from the levels detected in older isolates (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted using method as previously described (Kang et al, 2010) with some modifications. Various E. coli isolates was assigned to different phylogenetic groups according to method described by Clermont et al (2000) with some modifications using polymerase chain reaction (PCR).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the use of fluoroquinolones to treat flocks with FT is also a common practice in egg-producing farms (Penha Filho et al, 2016). Multi-resistance has been found in strains from Korea (Lee et al, 2003;Kang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%